LIVING CURRICULUM CONCEPT IN SIKL (INDONESIAN KUALA LUMPUR SCHOOL) - Mohamad Faisal Subakti; Partono Partono; Laily Rizqi Amalia; Nor Faela Shofa Afrida; Zumratun Nisak (JURNAL TARBIYAH, 2020)
This study aims to explain the concept of a living curriculum when it is applied in educational institutions. Indonesian Kuala Lumpur School is as an example of the concept of a living curriculum School. Specifically, this study discusses about the concept of a living curriculum as a curriculum which is relevant to the growing era. It is suitable, if it  applied in the the industrial era 4.0 to face the industrial era  5.0. This study was structured by using a systematic literature review method which is aimed to identify and interpret  research results related to the living curriculum. Meanwhile, the data analysis technique uses the flow model,  proposed by miles and hubermen. it includes data reduction, data presentation, and conclusion drawing. The results of this study indicates the importance of curriculum development which must stay relevant to the progress of the times, in producing of superior students and have global competitiveness.